Sadian per-versions (Leopoldo María Panero / Angélica Liddell) - Trueba Mira, Virginia (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper analyzes, from the framework of the reception of the Marquis de Sade after the Second World War, the reading of Sade made subsequently by Leopoldo María Panero and Angélica Liddell. Panero and Liddell share the same horizon of thought and the same philosophical and literary references, as it will be shown here with regard to two issues that directly touch the Sadian universe: law (writing) and the body (sexuality). It will be studied how both Panero and Liddell, in their theoretical texts and in their poetic and / or dramatic practice, incorporate the notion of perversion in Sade’s sense to deconstruct out of it, and with a clear ethical drive, categories of symbolic order, among them, and especially, those mentioned of law and body.